A Microfluidic Biosensor for Quantitative Detection of Salmonella in Traditional Chinese Medicine - Yutong Wu; Yang Liu; Jinchen Ma; Shanxi Zhu; Xiaojun Zhao; Huawei Mou; Xuanqi Ke; Zhisheng Wu; Yifei Wang; Sheng Lin; Wuzhen Qi (Biosensors)
Microbial contamination is an important factor threatening the safety of Chinese medicine preparations, and microfluidic detection methods have demonstrated excellent advantages in the application of rapid bacterial detection. In our study, a novel optical biosensor was developed for the rapid and sensitive detection of Salmonella in traditional Chinese medicine on a microfluidic chip. Immune gold@platinum nanocatalysts (Au@PtNCs) were utilized for specific bacterial labeling, while magnetic nano-beads (MNBs) with a novel high-gradient magnetic field were employed for the specific capture of bacteria. The immune MNBs, immune Au@PtNCs, and bacterial samples were introduced into a novel passive microfluidic micromixer for full mixing, resulting in the formation of a double-antibody sandwich structure due to antigen–antibody immune reactions. Subsequently, the mixture flowed into the reaction cell, where the MNBs-Salmonella-Au@PtNCs complex was captured by the magnetic field. After washing, hydrogen peroxide-tetramethylbenzidine substrate (H2O2-TMB) was added, reacting with the Au@PtNCs peroxidase to produce a blue reaction product. This entire process was automated using a portable device, and Salmonella concentration was analyzed via a phone application. This simple biosensor has good specificity with a detection range of 9 × 101–9 × 105 CFU/mL and can detect Salmonella concentrations as low as 90 CFU/mL within 74 min. The average recoveries of the spiked samples ranged from 76.8% to 109.5%